(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The issue of imbalance for women is more social than legal. As respects to the law, aside from personal issues, disparities in the arrangements of law are not really found. Personal issues, be that as it may, are controlled by religious laws or traditions. In the legal system however these laws or traditions are joined independently under the head of Personal Law, these are not, in any case, overall got from religious laws or traditions. A few changes through presenting enactments or declaring laws were made in their application. All things considered, these have been lacking to set up balance amongst women and men. This paper demonstrates how Muslim women are being treated as to their Personal Law, specifically Marriage and divorce law. Winning social developments of sexual orientation are as yet a crucial deterrent in understanding the requests of existing law. Keeping in mind the end goal to expel disparities and force justice, especially in marriage-related issues.